Efficacy of Single Formula of Clove, Eucalyptus, Neem and Citronella Oil against Budok Disease of Patchouli - Sri Yuni Hartati; NFN Sukamto; Nuri Karyani; NFN Zulhisnain (Buletin Penelitian Tanaman Rempah dan Obat, 2017)
Budok is one of the most important patchouli diseases caused by Synchytrium pogostemonis, spread out through seeds, soil, and water. A research to develop botanical pesticides based on essential oils was conducted at Indonesian Spices and Medicinal Crop Research Institute  in 2014. The research was aimed to evaluate the efficacy of single formula of clove, eucalyptus, neem, and citronella oil against budok disease. Research was conducted in disease endemic area in Cimanggu Research Installation, Bogor. Single formula of clove, eucalyptus, neem, and citronella oils were tested their efficacy against budok disease. Two synthetic fungicides of benomyl and bourdeaux mixture were used as comparison, and water as control. One month-old healthy patchouli plants were sprayed with each essential oil (5ml.l-1), benomyl (3 g.l-1), and bourdeaux mixture (1%) every two weeks for 5 times respectively. Experiment was arranged in  randomized completely block design (7 treatments, 3 replication, and 20 plants/replication). Neem oil was the most effective formula in suppressing budok disease  incidence  (58.30%)  compared to citronella (33.30%), clove (26.65%), and eucalyptus (8.30%), although it was still lower than benomyl (100%) and bourdeaux mixture (100%). Application of neem oil, benomyl, and bourdeoux mixture could inhibit S. pogostemonis infection and budok disease development. However, the application of clove and citronella oils only capable of inhibiting budok disease development. Those tested essential oils are potential to be developed as botanical pesticides to control budok disease of patchouli. However, their efficacy should be increased by producing formula mixtures of those essential oils.